Representasi Perempuan dalam Literasi Anak: Analisis Isi Buku Cerita - Husna, Nailul (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2024)
This study explores the representation of women in children's storybooks through in-depth content analysis. The study found that female protagonists are often portrayed in stereotypical traditional roles, such as loving mothers or supportive friends, while male protagonists tend to be portrayed as strong and courageous leaders. Female supporting characters also tend to have passive and subordinate roles, often only as a complement to the male main character. The narratives in many children's storybooks reinforce gender stereotypes, despite increased efforts to raise themes of equality and women's empowerment. Illustrations in storybooks also play an important role in reinforcing or challenging gender perceptions, with women often depicted in domestic activities and men in more active activities. The results of this study emphasize the importance of creating a more inclusive and diverse children's literacy to form a fairer and more balanced gender perception among children.